Marketing Strategy Analysis and Distribution Channels at Ibu Rokayah's Spicy Noodles in Tanjungkerta - Mardiansyah, De Aulia Ananda; Shintiana, Nova; Fatimah, Nurul Sri; Septiani, Vina; Kustiana, Riki (SINTESA, 2024)
This research aims to analyze the marketing strategy and distribution channels implemented by one of the MSMEs, namely Mie Pedas Sistik Ibu Rokayah in Tanjungkerta. Spicy Sistik Noodles are a typical culinary product that has great potential to develop in local and regional markets. In this research, a qualitative descriptive approach was used with data collection methods through in -depth interviews, observation and documentation studies. The research results show that the marketing strategy implemented by Ibu Rokayah's Spicy Sistik Noodles focuses more on a marketing approach by sending products to third parties (such as wholesalers, shops, distributors and resellers) in large quantities. Apart from that, this spicy cystic noodle business utilizes direct relationships with consumers by welcoming consumers who buy its products to the production site and utilizing online markets such as E-commerce and social media to be able to reach a wider market share. In terms of distribution channels, this product relies more on indirect distribution through sales in grocery stores, snack shops, grocery stores and marketing via social media to expand market reach. This research also identifies the challenges faced by this business, such as limitations in managing efficient distribution channels and limitations in increasing brand awareness in the wider market. The advice given is to develop a digital-based marketing strategy and expand the distribution network through collaboration with various parties